Implementasi Supply Chain Management pada Industri Kebaya Sinar Bintang Boutique Menggunakan Dolibarr - Ni Luh Putu Yunia Swandewi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Bali is an area in Indonesia that is growing rapidly in the world of kebaya fashion. Sinar Bintang Boutique is SMEs (Small and Medium Enterprises) that produces and sells various models of modified Balinese kebaya. The problems in Sinar Bintang Boutique are errors in inventory management, difficulties in planning business resources, and delays in the production process. Based on the existing problems, most of the work is in the Supply Chain Management functional area. The solution is to do Business Process Re-engineering with the ERP concept with performance analysis using SCOR (Supply Chain Operation Reference). The new business processes are implemented and adapted to Dolibarr opensource software integration with DoliDroid, making it easier for users to access the system. The final stage in this research is using a User Acceptance Testing questionnaire and a Likert Scale to assess the level of user satisfaction of the Dolibarr application. The results of the survey are an average percentage value of statements with the convenience aspect which is 64%, the average percentage value of statements in the usefulness category is 90%, and the total percentage of questions in all categories is 77% with a conclusion of the score interpretation criteria that is good.